Complete Genome Sequence of Chlamydia abortus MRI-10/19, Isolated from a Sheep Vaccinated with the Commercial Live C. abortus 1B Vaccine Strain - Livingstone, Morag (2021)
We report the complete genome sequence of Chlamydia abortus MRI-10/19, recovered from the infected placenta of a sheep that had been vaccinated with the commercial live attenuated C. abortus 1B vaccine strain. Comparative analysis revealed 1 single nucleotide polymorphism (SNP) difference and 4 indels compared to the vaccine strain.